Sclerosing Epithelioid Mesenchymal Neoplasm of the Pancreas: Case Report and Literature Review of the Morphologic Characteristics. Issue 5 (May 2021) - Shitani, Masahiro; Ogino, Jiro; Isosaka, Mai; Ito, Miki; Fujino, Hiroki; Ota, Shigenori; Tayama, Yoshiko; Adachi, Takeya; Tsuruma, Tetsuhiro; Hirata, Koichi; Nakase, Hiroshi
Abstract : Supplemental digital content is available in the text.